Assessing the Utilisation Regime of Ghana’s Oil Revenue under the Petroleum Revenue Management Act - Kwakye, Chris Adomako- (Journal of Ecohumanism, 2024)
Ghana’s Petroleum Revenue Management Act (PRMA) created two funds under the Act. The first comprises the Petroleum Holding Fund, the Ghana Petroleum Funds made up of the Ghana Stabilisation Fund and the Ghana Heritage Fund, referred to as Sovereign Wealth Funds (SWFs), and the Annual Budget Funding Amount (ABFA), which is subject to the accountability regime under the PRMA. The second, consist of the Consolidated Fund and the Contingency Fund, exists outside the PRMA; nevertheless, these funds receive a portion of Ghana’s oil revenue. The PRMA has established an accountability regime to ensure effective oil revenue management by giving the Public Interest Accountability Committee (PIAC) and the Auditor-General the mandate to examine oil revenue management. Be that as it may, the second set of funds is not subject to the accountability regime existing under the PRMA. The article sees the practice as a disturbing trend and argues that the PRMA must be amended to allow the institutions to evaluate oil revenue management for accountability to prevail.